The Role of Dynamic Digipreneur Capabilities in Mediating The Relationship Between Digital Transformation and Competitive Advantage in Improving Business Performance - Henny Diana Erlany; Ngatno Ngatno; Bulan Prabawani; Reni Shinta Dewi (Ridwan Institute, 2023)
This research aims to investigate the relationship between digital transformation, dynamic digital entrepreneur capabilities, competitive advantage, and business performance in small and medium enterprises (IKM). The first hypothesis (H1) proposes that digital transformation has a positive effect on competitive advantage, referring to Porter's (2001) view on the role of the internet in creating competitive advantage through partnerships and business digitalization. The second hypothesis (H2) states that digital transformation influences dynamic digipreneur capabilities through increasing knowledge sharing and digital capabilities. The third (H3) and fourth (H4) hypotheses claim that entrepreneurial-oriented dynamic digital entrepreneur capabilities have a positive impact on the competitive advantage and business performance of SMEs. The fifth hypothesis (H5) confirms that competitive advantage contributes to improving SME business performance through increasing market share, profits, efficiency, reputation and marketing effectiveness. Next, the sixth (H6) and seventh (H7) hypotheses try to explore the role of mediation, with H6 proposing that dynamic digipreneur capabilities can mediate the relationship between digital transformation and competitive advantage, and H7 claiming that competitive advantage can mediate the relationship between digital transformation and SME business performance . Finally, the eighth (H8) and ninth (H9) hypotheses suggest a dual mediating role, with H8 proposing that competitive advantage can act as a mediator between dynamic digipreneur capabilities and SMI business performance, while H9 proposes that digital transformation can influence SMI business performance through digipreneur capabilities dynamic and competitive advantage as a mediator.